2019
DOI: 10.1680/jgele.18.00231
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission monitoring of crushing of an analogue granular material

Abstract: A two-dimensional analogue material formed of rod cylinders of chalk is tested under onedimensional oedometric loading conditions. Passive non-destructive Acoustic Emission (AE) monitoring technique is used to document the occurrence of crushing of individual particles. While the AE activity is recorded by a sensor placed on the sample boundaries, the AE signals are also corroborated with the observations based on video records of the exposed face of the 2D sample, as well as vertical loading and displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…An acoustic wave in granular soils generally stems from particle interactions such as particle sliding or crushing. Extracting and interpreting the parameter information (e.g., AE hit or energy rate) carried by AE waveforms provides a quantitative analysis of the failure level in a stressed material [8,[28][29][30][31][32][33][34][35]. Dixon et al [36] reported the availability of AE technique combined with active waveguides in terrigenous type soil slope monitoring through field trials, and a relation between AE rate and deformation rate of soil was established to evaluate the stability of soil slopes.…”
Section: Introductionmentioning
confidence: 99%
“…An acoustic wave in granular soils generally stems from particle interactions such as particle sliding or crushing. Extracting and interpreting the parameter information (e.g., AE hit or energy rate) carried by AE waveforms provides a quantitative analysis of the failure level in a stressed material [8,[28][29][30][31][32][33][34][35]. Dixon et al [36] reported the availability of AE technique combined with active waveguides in terrigenous type soil slope monitoring through field trials, and a relation between AE rate and deformation rate of soil was established to evaluate the stability of soil slopes.…”
Section: Introductionmentioning
confidence: 99%